2022
DOI: 10.3389/ijph.2022.1604452
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Management for People With Hypertension

Abstract: Objectives: To assess the effectiveness of continuity of care policies by identifying the impact of a chronic disease management program on the continuity of care in patients with hypertension in South Korea.Methods: The propensity score matching method was used to control selection bias, and the difference-in-differences method was used to compare the impact on the treatment and control groups according to the policy intervention.Results: The continuity of care index of hypertensive patients using the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The primary healthcare chronic disease management pilot project aimed to ensure continuous management of patients with high blood pressure and diabetes who visited neighborhood clinics and is in the process of converting to a main project. Several studies have shown that primary care-centered chronic disease management is cost-effective and improves COC and medication adherence [43][44][45][46]. To improve COC, it is important to introduce policies at the national level and make steady efforts to manage health at the individual level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary healthcare chronic disease management pilot project aimed to ensure continuous management of patients with high blood pressure and diabetes who visited neighborhood clinics and is in the process of converting to a main project. Several studies have shown that primary care-centered chronic disease management is cost-effective and improves COC and medication adherence [43][44][45][46]. To improve COC, it is important to introduce policies at the national level and make steady efforts to manage health at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…The COC is considered a reliable measure because it is used in the absence of routine visits by healthcare providers and is less sensitive to the number of visits by healthcare providers [ 23 ]. The COC indicator has the advantage of considering the number of healthcare providers and the number of visits together [ 12 ]. The COC has a value between 0 and 1, and the closer it is to 1, the better the COC [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a common chronic disease that requires continuous treatment and management [7]. Self-care practices at home are known to have potential benefits for Healthcare 2023, 11, 2182 2 of 16 managing hypertension [8].…”
Section: Introductionmentioning
confidence: 99%